Biochemical changes associated with non-alcoholic fatty liver disease in response to berberine treatment: a systematic review and meta-analysis of clinical and preclinical research - Zhu, Wenyu; Yang, Lele; Dai, Yufan; Wang, Hanyang; Zhou, Jiaxuan; Xia, Lina; Shen, Tao (Frontiers in Pharmacology, 2025)
BackgroundNon-alcoholic fatty liver disease (NAFLD) represents a global health challenge. Berberine, an isoquinoline alkaloid traditionally used for metabolic disorders, has garnered attention for its potential therapeutic interventions.ObjectiveTo comprehensively review and perform a meta-analysis of berberine’s effects on NAFLD across clinical and preclinical studies.MethodsA comprehensive literature search was conducted across five databases from their inception to May 2024. We included randomized controlled trials and animal studies that evaluated berberine’s impact on NAFLD using specified biochemical markers.ResultsOut of 487 screened studies, 22 (4 clinical and 18 preclinical) were included. Clinically, berberine significantly reduced fasting blood glucose (FBG) levels, with an effect size of 0.53 (95% CI: 0.04–1.01). In preclinical settings, berberine consistently demonstrated benefits across several markers, including alanine aminotransferase (ALT), aspartate aminotransferase (AST), and lipid profiles, despite significant heterogeneity in some outcomes.ConclusionBerberine presents promising therapeutic avenues for NAFLD management, especially in terms of glucose metabolism. Further rigorous, well-designed trials are needed to substantiate these findings.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, Identifier CRD42023459618.